Spreading of Groundwater Contamined by Leached in the Surrounding Area of Piyungan Landfill Bantul District, Yogyakarta Province - J Sartohadi; M Widyastuti; I. Sri Lestari (Forum Geografi, 2005)
The objectives of this research are: (1) to study the characteristics of aquifer, distribution and chemical types of groundwater in the research area; (2) to measure the consentration of major elements (HC03-, Cl-, S042-, Ca2+, Mg2+, Na+, K+) and minor elements (S2-, NH4+) as indicators of leached contamination in the groundwater; and (3) to establish the spreading of contamined groundwater by leached. The grid sampling method was applied in this research. The grid dimension is 1 cm x 1 cm measured in the 1:25000 scale of Indonesian Topographic Map. The groundwater samples were taken randomly within the grid. Not the whole study area covered by the map was grided but only the surrounding area of Piyungan Landfill and the area lower than Piyungan landfill were grided. The groundwater samples were taken during the rainy season because during the rainy season there were more leached produced from Piyungan Landfill. The groundwater samples were examined their physical and chemical qualities using the legal standard quality in Yogyakarta Province. Spatial analysis using maps and graphics were applied to examine the spreading of contimined groundwater by leached. The spreading of unconfined groundwater in the study area was not equal distributed but it seems to be controlled by the landforms. There were an increasing elements content of Cl-, Ca2+, Mg2+ and HCO3-, as well as dissolved oxygen, NO3- and S2- in the groundwater contamined by leached. The zonation of the spreading of groundwater contamined by leached was categorized into three class, i.e., central (location of landfill, well number 1 0), transisional (well number: 11, 12, 13, 15), and primary (well number: 8, 14, 16, 17, 25, 26) zones. The zonation of groundwater matched with the analysis of groundwater quality by the distance from the Piyungan Landfill.